COMPANY PROFILE AUTORUN CD CV. ANGELSOFT APPLICATIONS USING MACROMEDIA FLASH MX 2004 - Veronica Olivia Kartika; Marzuki Marzuki,Skom.,MMSI (Jurnal Sistem Informasi, 2006)
Company Profile autorun CD is a company profile and information that can be run automatically by a computer. Company Profile can be used to replace the company profile for this company which was just a series of papers in the collection of paper bound together with an unattractive appearance and become dull and even difficult to draw the attention of prospective clients. Given this CD Autorun Company Profile, companies can have an advantage, with an attractive and dynamic design by integrating text and images on the Company Profile can attract prospective clients to consider the company profile and information and ultimately attracted to cooperate. Time and effort can be more deficient in terms of promotion but gained huge profits. To view a dynamic and interesting, can use Macromedia Flash MX 2004, while to be able to autorun the CD fil with SWF extension can be made into a file with an EXE extension.